THE PROBLEM ANALYSIS OF DISTANCE LEARNING ORGANIZATION OF SPATIAL RELATIONS AND GEOMETRICAL FIGURES FOR FUTURE TEACHERS OF PRIMARY EDUCATION (Education in the 21st Century, 2023)
The study of spatial relations and geometrical figures has its own peculiarities at "Primary Education" in pedagogical institutions of higher education. The article presents the analysis of the organization of studying the mathematics course by future teachers of primary education during distance education. The general logical methods of systematization and generalization of the experience of higher education institutions specializing in "Primary Education" were used for the study. The main problems have been considered and the ways to overcome them have been given. It has been found out that the main problem is the result of students' independent work. There are several reasons for this, such as their inability to overcome a large volume (more than 60%) of the material allocated for self-learning in connection with the low level of self-education skills, as well as insufficient adaptation of the content of the "Mathematics" course (lack of geometrical material), effective means of organization of students' independent work. The article provides the analysis of identified problems and possible ways to eliminate them. A conclusion is made on the directions and according to which factors it is necessary to improve the content of the mathematical training of future teachers of primary education and educational materials for distance learning. It is noted that the issues of organization of the independent work of future teachers of primary education when studying spatial relations and geometrical figures in conditions of informational and educational environment are important and need to be resolved, there is a constant need to change teaching methods. The problems that arise during the organization of independent work of students during online practical classes are considered, attention is drawn to the positive and negative aspects of the distance form of conducting classes and the prospects of further research on improving the effectiveness of the mathematical training of future teachers of primary education in the conditions of distance learning. Due attention is paid to the implementation of distance learning of future teachers of primary education in spatial relations and geometrical figures with the help of information technologies, which contribute to the revitalization of cognitive activity of students during their independent work.
Keywords: distance learning; mathematical training; future teachers of primary education